Evaluasi Kinerja dengan Pendekatan Balanced Scorecard di Poliklinik Unit Rawat Jalan RSUD Andi Djemma Masamba, Sulawesi Selatan - Santika, Made; Yuliaty, Farida; Wirawan, Chevie (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2025)
Balanced scorecards are often used in various organizations, including hospitals, because they are able to measure performance in a comprehensive, consistent, measurable and balanced manner. Until now, performance measurement in the outpatient clinic of Andi Djemma Regional Hospital still focuses on financial aspects only. This research aims to analyze polyclinic performance using the balanced scorecard method through four main perspectives: finance, customers, internal business processes, and growth and learning. The research method applied is a quantitative descriptive approach. Performance data was collected from hospital secondary data for 2023 and previously, as well as primary data through questionnaires involving patients and employees. The results of the analysis show that performance from a financial and customer perspective is classified as "fair," the internal business process perspective is rated as "good," while the growth and learning perspective is also in the "fair" category. Overall, the performance of the outpatient clinic at RSUD Andi Djemma Masamba is in the "fair" category, with a score of 0.57 which indicates a medium level of performance.